PENYELESAIAN SENGKETA KEWENANGAN PENYIDIKAN TINDAK PIDANA KORUPSI PENGADAAN SIMULATOR SURAT IZIN MENGEMUDI ANTARA POLISI REPUBLIK INDONESIA DAN KOMISI PEMBERANTASAN KORUPSI (JURNAL HUKUM SEHASEN, 2015)
Authority dispute between the Indonesian National Police and the Commission for the eradication of corruption is a dispute of authority in the eradication of corruption Corps Traffic Police on the procurement of a driver's license. Both of these law enforcement agencies alike want to handle traffic cases in the Police Corps. KPK and the police have the same powers of inquiry and investigation under the Act are held by law enforcement agencies. KPK use Law No. 30 of 2002, while the police by Undang0undang No. 2 of 2002. In the dispute over state institutions can not be left alone then it must be resolved constitutionally according to applicable legislation. From the results of this study was found the answer to the problem formulation is that disputes this institution is under the authority of the constitutional court to resolve because the agency KPK kewenagannya taken by police agencies, both state agencies is a state institution whose authority granted by the 1945 Constitution Based on Article 24 C of paragraph (1) of this that the constitutional court must resolve this dispute the authority of state institutions. Keywords: Authority, the Commission, the Police, and the Constitutional Court.